Efforts to increase mental toughness through cognitive behaviour modification for paser club archery athletes - Fitri Nur Shouma Ramadani; Fithri, Rizma; Kusumawati, Estri (Talenta Publisher, 2025)
Sports competitions are one of the arenas in which a country can prove its capability to manage quality human resources. Good mental ability management is one factor that influences an athlete's success rate in winning a competition. Mental toughness positively influences an athlete, one of which is fostering motivation to achieve. This study aimed to determine the effect of CBM intervention on Paser club archery athletes in Sidoarjo in terms of increasing Mental toughness. This study uses a pretest-posttest design type with a single group and experimental research methodology. Because the sample is less than 30, the sampling technique used is non-probability sampling, namely saturation sampling. The mental toughness scale is used as a data collection tool and analyzed using a paired t-test. The statistical test results showed a significance value of .0001, which means that there is an effect of CBM intervention in increasing the mental toughness of Paser club archery athletes in Sidoarjo.